(untitled) (American Journal of Medical Science and Innovation, 2023)
Activities, environment, work style, living standards of housewives in Bangladesh vary from place to place. Housewives face many musculoskeletal problems related to housework and quality of life. Hence the aim of our investigation is to investigate the prevalence of joint pain among rural and urban housewives of Bangladesh. An attempt was made to compare joint pain in urban and rural housewives. A sample was selected to assess and comparison of joint pain prevalence among 400 unemployed urban and rural housewives aged 25–60 years in Bangladesh. Regression analysis was performed on their socio-economic and joint pain information through interviews with questionnaires. Data analysis shows that urban housewives have relatively higher prevalence of joint pain than rural housewives and it is 70.5% and 58.5% respectively. Odds ratio (OR) and 95% confidence interval (CI) comparing joint pain in Bangladeshi housewives adjusted for age and BMI showed that the prevalence of knee and low back pain was highest and was associated with age and BMI. This study showed that joint pain was significantly higher in urban housewives compared to rural housewives. Bangladeshi housewives suffer from knee and lower back pain the most. Their joint pain prevalence is increases with age and BMI. Joint pain in housewives may be related to obesity, occupational differences and environmental factors. In addition to daily household work, urban housewives can perform some simple physical exercise regularly, which can improve their mobility and strength as well as reduce the rate of obesity.